Pengaruh Pemasaran Online Terhadap Keputusan Konsumen Depot Air Minum Mulia di Kelurahan Mampu - Ratih Suwanti (STIE Amkop Makassar, 2024)
The results of this study indicate that based on the partial test Product and Place have a positive but insignificant effect while price, promotion, employees, physical evidence and processes have a positive and significant effect, while the results of the simultaneous test of products, prices, places, employees, physical evidence and processes have a positive and significant effect. simultaneous positive and insignificant effect on Customer Decisions in drinking water company.